Usability assessment for the enhancement of quality of a web portal interface - Ramachandran, Shageetha; Nor, Rozi Nor Haizan; Jusoh, Yusmadi Yah (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
A web portal can be defined as a personalized, single point of access to information, resources and services covering a wide range of topic. Based on some researches, a system based on the internet can improve the work efficiency to some extent and provide all kinds of academic administration information timely. As to establish the intended function, usability is a crucial factor to be embarked on. This will ensure that the users are attracted to use the portal by increasing the relationship between the users and the portal’s interface. The Applied Informatics Research Group (AIRG) is the group assigned by the Faculty of Computer Science and Information Technology (FSKTM) to manage the Research Group Portal System (RGPS) that is the sample used in this research. The RGPS is a web-based system that allows collaboration among the users; to locate, store, use and share their knowledge. The main objective of this research is to obtain the feedbackfrom the users regarding the usability of the RGPS that is deterring them from optimizing the usage of this system. Surveys and questionnaires are used to evaluate and the output acts an input to modify the interface of the RGPS. Again, validation will be done to weight the users’ experience with the modified user interface.